Supraspinal Modulation : Something to be Remembered - Parami, Pontisomaya; Senapathi, Tjokorda Gde Agung; Suarjaya, I Putu Pramana; Lolobali, Marilaeta Cindryani (Bali Journal of Anesthesiology, 2018)
Pain had always been a challenging issue in patients with acute and chronic condition. Â Pain results from activation of sensory receptors specialized to detect actual or impending tissue damage. However, a direct correlation between activation and nociceptors and the sensory experience of pain is not always apparent. Emotional state, the degree of anxiety, attention and distraction, past experiences, memories, and many other factors can either enhance or diminish the pain experience.Many active agents are used to block and alleviate pain sensation in acute and chronic settings. When an inadequate treatment for acute pain and neuralgia occurred, it would induce complex processes involving both central and peripheral sensitization contributing to persistent post-surgical pain and worsening neuralgia that would lead to chronic pain issue.The important thing to be considered is that this pain process is an intertwined and interconnecting and sustainable process that could not be cut abruptly. Our aim is to remind us to accept that pain pathway is merely not one straight way but still a convoluting idea which could still revolve and expand. Imagining areas could be defined surely one day through high technology advances and would lead us into defining the depth of this beautiful yet complex pathway.